Basic primary care approach: providing community with education and hands on training regarding diabetes care - May, Khin Soe; Mohamed Nazar, Nor Ilyani (Malaysian Pharmaceutical Society, 2015)
With an alarmingly increased rate of the prevalence of diabetes and unsatisfactory quality of care among diabetes patients become the major issues. Viewing this, Kulliyyah of Pharmacy, IIUM had made an initiative to conduct a "Diabetes Education Workshop with Hands on Training on handling related devices. The aim of workshop was not only to educate the diabetes patients and care givers but also to train them in handling of the useful devices. The activity of workshop included lectures by experienced health care providers and demonstration of devices and hands on training by experienced lecturers and laboratory personals. Questionnaires were distributed to all participants to evaluate their background knowledge related with diabetes prior to the lectures and training. Moreover, the participants' RBS, FBS and other physiological parameters were also checked and recorded. Total 66 participants who were 24 administrative staffs and 9 laboratory staffs from various faculties, 18 nurses, 14 care givers and a pharmacist attended. They were male 14 (21.2%) and female 52 (78.8%) and 61 (92.44%) Malay, 4 (6.1%) Chinese and only one (1.5%) Indian. Mean BMI value was 24.92 ±4.66, mean RBS 6.63±1.32 mmol/L, mean FBS 5.13±0.52 mmol/L, mean SBP 113.94±13.35 mmHg and mean DBP 74.13±10.86 mmHg were observed. Two male (3.3%) and 14 female (23.7%) were found to be abdominal obesity. Forty nine (74.2%) responded that they were satisfied with the knowledge and skill they gained from program and requested to continue it in next years. Such useful program is suggested to collaborate with other Universities in future.